2020
DOI: 10.1158/2159-8290.cd-19-0384
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cells Exhibit Metastatic Tropism and Reveal Brain Metastasis Drivers

Abstract: Hematogenous metastasis is initiated by a subset of circulating tumor cells (CTC) shed from primary or metastatic tumors into the blood circulation. Thus, CTCs provide a unique patient biopsy resource to decipher the cellular subpopulations that initiate metastasis and their molecular properties. However, one crucial question is whether CTCs derived and expanded ex vivo from patients recapitulate human metastatic disease in an animal model. Here, we show that CTC lines established from patients with breast can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(99 citation statements)
references
References 55 publications
6
93
0
Order By: Relevance
“…Gene expression profiling of CTCs in metastatic breast cancer suggests that CTCs that are associated with brain metastasis have increased activity of the Notch signaling pathways, along with an increase of pro-inflammatory chemokines (TNF, IL1β, and NF-κB), immunomodulatory networks (CXCL8, CXCR4, CD86), and mitogenic growth factors (PDGF-BB) [72]. In a separate study, a genome-wide assessment of CTC lines established from breast cancer patients suggests that copy-number gain of SEMA4D (a mediator of blood-brain barrier transmigration) and overexpression of MYC are novel markers for brain metastasis [41]. More generally, however, additional work will be needed to dissect the genetic requirements for organo-tropism of CTCs in several cancer types, and the identification of the fundamental networks that are involved might aid metastasis prevention strategies.…”
Section: Clinical Value Of Ctcsmentioning
confidence: 97%
“…Gene expression profiling of CTCs in metastatic breast cancer suggests that CTCs that are associated with brain metastasis have increased activity of the Notch signaling pathways, along with an increase of pro-inflammatory chemokines (TNF, IL1β, and NF-κB), immunomodulatory networks (CXCL8, CXCR4, CD86), and mitogenic growth factors (PDGF-BB) [72]. In a separate study, a genome-wide assessment of CTC lines established from breast cancer patients suggests that copy-number gain of SEMA4D (a mediator of blood-brain barrier transmigration) and overexpression of MYC are novel markers for brain metastasis [41]. More generally, however, additional work will be needed to dissect the genetic requirements for organo-tropism of CTCs in several cancer types, and the identification of the fundamental networks that are involved might aid metastasis prevention strategies.…”
Section: Clinical Value Of Ctcsmentioning
confidence: 97%
“…Besides the elimination of CTCs, blocking metastatic progression could be more effective in the case of killing primary cancer cells that are a source of metastasis-initiating CTCs. As suggested by Klotz and colleagues [94], targeting of SEMA4D and GPX1 in primary tumors can be a potential therapeutic approach for the abrogating ability of CTCs to colonize the brain and for preventing brain metastasis in BC patients. This therapy would be an innovative strategy to prevent metastasis at an early stage and even before the tumor is clinically diagnosed.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, amplification of 8q24.21, as well as chromosome 9q in CTCs, was found to be a clonally selected event for the initiation of brain metastasis in BC. It turned out that overexpression of semaphorin-4D (9q) promoted CTCs transmigration through the blood-brain barrier whereas MYC (8q24.21) facilitated the adaptation of tumor cells to the activated brain microenvironment via upregulation of GPX1 enzyme [94].…”
Section: Genetic Heterogeneitymentioning
confidence: 99%
“…Several studies have shown successful ex vivo expansion of CTCs isolated from patients with breast 7 , colorectal 8 , and prostate 9 cancer. These CTC lines have provided sufficient amounts of material for many analyses, including xenograft analysis and drug susceptibility assessment 7,10 .…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported a method for the ex vivo culture of CTCs derived from metastatic breast cancer patients and established several CTC lines 7 . These CTC lines exhibit metastatic potential that represents the major metastatic lesions in corresponding patients 10 . In addition, they are cultured in suspension and physiological oxygen level, mimicking the environment of CTCs in venous blood circulation.…”
Section: Introductionmentioning
confidence: 99%